2021
DOI: 10.1186/s12906-021-03338-7
|View full text |Cite
|
Sign up to set email alerts
|

The trends of complementary alternative medicine use among cancer patients

Abstract: Background The use of complementary and alternative medicine (CAM) is common among cancer patients and it may reflect the individual and societal beliefs on cancer therapy. Our study aimed to evaluate the trends of CAM use among patients with cancer between 2006 and 2018. Methods We included 2 Cohorts of patients with cancer who were recruited for Cohort 1 between 2006 and 2008 and for Cohort 2 between 2016 and 2018. The study is a cross-sectional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…As a result, they may use CAM more frequently to alleviate stress and enhance their immune systems ( 51 ). However, alternative indications for the use of CAMs include cancer treatment and symptom management, such as pain control and appetite enhancement ( 24 ). Albabtain et al discovered that many women used CAM to improve their physical and emotional wellbeing, with the primary cause being improved immune system function ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result, they may use CAM more frequently to alleviate stress and enhance their immune systems ( 51 ). However, alternative indications for the use of CAMs include cancer treatment and symptom management, such as pain control and appetite enhancement ( 24 ). Albabtain et al discovered that many women used CAM to improve their physical and emotional wellbeing, with the primary cause being improved immune system function ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the critical issue is to convince patients to consult with doctors, which requires cultivating a culture and educating patients in this regard. A study conducted between 2006 and 2008 as well as between 2016 and 2018 found that disclosure of CAM use had not changed significantly over time and remained low (31.6–35.7 percent), indicating that additional research and interventions are needed to identify the causes and increase disclosure of information to physicians by cancer patients ( 24 ). Furthermore, the absence of management advice and data on the quantity and quality of CAM-related recommendations in clinical practice guidelines (CPGs) for treatment or management demonstrates a significant gap in the necessary guidance for physicians and clinical researchers ( 56 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies in Iran have found that a high percentage of Iranians use complementary and alternative medicine [ 22 25 ]. Numerous studies demonstrate that CAM is widely used by cancer patients, and some studies’ findings indicate a rise in the usage of CAM or its use over the last decade [ 26 ]. During crises such as the outbreak of COVID-19, some types of CAM, especially dietary supplements, herbs, and prayers, are commonly used to prevent COVID-19 and reduce the anxiety caused by the epidemic [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, this is the fastest-growing supply in the country, with a more than 200% increase in the number of services and the one with the highest number of services offered per population 2.20/100000 inhabitant 6 . Studies have shown that yoga and meditation have also been presented as spiritual practices, used mainly for people affected by cancer and other chronic conditions to promote health and quality of life 39,40 .…”
Section: Discussionmentioning
confidence: 99%